Fotobiomodulação associada a material carbonoso particulado impregnado com partículas de nanoprata no reparo ósseo - Assirati, Paulo Henrique Boulitreau (2019)
In Brazil, thousands of musculoskeletal surgeries are performed annually and this high number of procedures produces a social and economic impact for the country. Photobiomodulation is already considered an auxiliary therapy mainly in the postoperative period, with influence on the painful process and the bone repair. The use of particulate carbon material has been suggested by our research group as an alternative bone substitute and its impregnation by silver has been shown to be effective in the control of bone infections. The aim of this work was to evaluate the effect of photobiomodulation on the bone repair, after the use of carbon biomaterial impregnated with nanoprata in tibia of rats. Materials and methods: Male Wistar rats were anesthetized with a combination of ketamine and xylazine (90mg / kg and 10mg / kg) and submitted to the bone defect confection located in the monocortical region of the two hind tibiae. The animals were randomly assigned to 5 groups: (I) untreated lesion (NT), (II) treated with pure carbon material (CM), (III) nanoprate impregnated (CM + NS) and (IV) treated exclusively with phototherapy (PBM). The fifth group (V) showed the association of phototherapy with silver impregnated carbonaceous material (CM + NS + PBM). The animals were irradiated on alternate days until the 12th day with 830nm, 6J, 100mW laser. Thirty days (30) after lesion induction, the animals were euthanized and tibia and blood samples were collected and stored for further analysis. Results: The CM, CM + NS and CM + NS + PBM groups presented increased levels of alkaline phosphatase. On the other hand, the PBM group presented reduction, all compared to the NT group. The CM + NS and CM + NS + PBM groups showed an increase in Fmax when compared to the NT group. Only the PBM group showed an increase in Dmax compared to the NT group. All treatments presented reduction in granulation tissue and better organization in the bone tissue compared to the NT group. Conclusion: The use of carbon material impregnated by silver seems to aid in bone repair. The treatment with photobiomodulation associated or not with silver impregnated carbon material aided in bone repair and recovery of the mechanical properties of this tissue.